Laser scanning confocal microscopy as a powerful tool for fracture surface characterization - Bábková, Petra; Matějka, Vlastimil (Manufacturing Technology Journal, 2010)
The aim of this paper is to show the applicability of the Laser Scanning Confocal Microscopy (LSCM) for the fractographical research of the compact tension specimens. Scanning Electron Microscopy (SEM) together with Light microscopy (LM) are prevailing techniques for the fracture surfaces examination [1,2]. Information about the surface topography obtained by LM and SEM is reflected in 2D image whereas LSCM provides 3D images. In this work the fracture surfaces of the compact tension specimen were examined by LSCM and by SEM and the main features as cleavage facets, ductile dimples, stretch zone and fatigue were observed.
Keywords: LSCM; SEM; fractography; 3D image